Overview of Public Health Examination Results in Tumbang Tahai, Palangka Raya, Central Kalimantan, Indonesia - Rian Ka Praja; Muhammad Naufa Anwar; Muhammad Ricko Fahrizal; Yan Antonio; Nadia Kesiha Amanda Br Ginting; Riccardo Hartoyo; I Dewa Gede Sandhikarana; Ni Nyoman Sri Yuliani (International Journal of Sustainable Applied Sciences, 2023)
As a developing country classified as low- and middle-income countries (LMICs), the disparity in knowledge regarding hypertension and Non-Communicable Diseases (NCDs) should be a concern for the government. Data from the 2018 Riset Kesehatan Dasar (Riskesdas) showed that the prevalence of hypertension in Central Kalimantan reached 34.47%, compared to 26.7% in the 2013 Riskesdas. The 2018 Riskesdas data also revealed that the prevalence of joint diseases in Central Kalimantan was 7.61%. Various factors such as socioeconomic status, dietary patterns, medication usage, and comorbidities can influence uric acid levels. In essence, achieving good health is a fundamental right for every individual, regardless of their economic and social status. However, in practice, healthcare services have not been able to reach the entire population of the country. To address this issue, Asian Medical Students’ Association (AMSA-UPR) conducted a community service in the form of free health examinations in Tumbang Tahai Subdistrict of Bukit Batu District in Palangka Raya, Central Kalimantan. The research employed a descriptive method with a quantitative approach based on blood pressure, blood glucose, and uric acid examinations. The results showed that many residents are still experiencing hypertension, but most have normal blood glucose and uric acid levels.